FDG PET Uptake as a Predictor of Pain Response in Palliative Radiation Therapy in Patients with Bone Metastasis - ALKIŞ, HİLAL; ADLI, MUSTAFA (RADIOLOGICAL SOC NORTH AMERICA, 2013)
Purpose: To evaluate the relationship between fluorine 18 fluorodeoxyglucose (FDG) positron emission tomography (PET) maximum standardized uptake value (SUVmax) and pain response to radiation therapy (RT) in patients with bone metastasis. Materials and Methods: Institutional ethical board approval for the study was obtained, with informed consent, for this prospective study. Thirty-one patients with metastatic bone pain who underwent FDG PET/computed tomography before RT were included. Patients were diagnosed with lung (n = 16), breast (n = 7), stomach (n = 2), and head and neck cancers (n = 3), as well as unknown primary tumor (n = 3). Eighty-five painful metastatic locations with FDG PET scans geographically corresponding to 40 treatment fields were evaluated. Pain scores using visual analog scale or faces pain rating scale and SUVmax at each location were recorded. All patients were treated with a single fraction 8 Gy RT. Pain scores after RT were assessed at weeks 2, 4, 8, 12, 16, 20, and 24. The pretreatment pain scores and pain response to RT were compared with FDG PET SUVmax of each location. Pearson correlation, independent t test, one-way analysis of variance, and chi(2) tests were used for statistical analysis. Results: Median SUVmax and initial pain scores for all locations were 7.2 (range, 1.5-22.5) and 6 (range, 2-8), respectively. Median follow-up time was 24 (range, 3-112) weeks. Median SUVmax was 4.5 (range, 3.1-7.3), 4.75 (range, 1.5-10.3), 8.8 (range, 5.2-11.9), and 12.1 (range, 7-22.5) for pretreatment pain scores of 2, 4, 6, and 8, respectively. SUVmax was correlated with pretreatment pain scores (P < .0001). SUVmax and pretreatment pain scores were also significantly associated with pain response to RT. Median SUVmax for locations with complete response, partial response, pain progression, and indeterminate response was 5.2, 9.75, 10.8, and 6.4, respectively (P <= .001). Conclusion: FDG PET SUVmax correlated with initial pain severity and pain response to RT and can be used as a predictive factor for treatment response in patients with painful bone metastasis treated with palliative RT. (C) RSNA, 2013
Keywords: POSITRON-EMISSION-TOMOGRAPHY; STANDARDIZED UPTAKE VALUE; SQUAMOUS-CELL CARCINOMA; BREAST-CANCER; LUNG-CANCER; NECK-CANCER; RADIOTHERAPY TRIALS; RECTAL-CANCER; HEAD; PROLIFERATION